2013
DOI: 10.3109/1547691x.2013.826307
|View full text |Cite
|
Sign up to set email alerts
|

PI3K-Akt/PKB signaling pathway in neutrophils and mononuclear cells exposed to N-nitrosodimethylamine

Abstract: Neutrophils (PMN) play diverse regulatory and effector functions in the immune system through the release of reactive nitrogen species, including nitric oxide (NO). The enzyme responsible for NO synthesis in PMN is inducible nitric oxide synthase (iNOS) that is regulated by various signaling pathways, e.g. PI3K-Akt/PKB, and transcription factors. N-Nitrosodimethylamine (NDMA), a xenobiotic widespread in the human environment, affects immune cells. The study objective here was to examine the role of the PI3K-Ak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
(43 reference statements)
0
14
0
Order By: Relevance
“…LPS is known to trigger NF-B activation through TLR4 signalling. However, studies have shown that dimethyl nitrosamine could be activating the PI3K-Akt/PKB pathway inimmune cells, which then contributes to the activation of NF-B [29].…”
Section: Discussionmentioning
confidence: 99%
“…LPS is known to trigger NF-B activation through TLR4 signalling. However, studies have shown that dimethyl nitrosamine could be activating the PI3K-Akt/PKB pathway inimmune cells, which then contributes to the activation of NF-B [29].…”
Section: Discussionmentioning
confidence: 99%
“…Carcinogens can stimulate cancer via the production of critical pro-inflammatory, pro-angiogenic and pro-tumorigenic cytokines/transcription factors, including TNF-α, IL-6, and NF-κB, as well as proto-oncogenes (e.g., c-Myc) ( Chen, Yan, & Ye, 1998 ; George, Tsuchishima, & Tsutsumi, 2019 ). Moreover, carcinogens may impair the host protective immune response via immunotoxicity, including increased apoptosis of leukocytes and reactive oxygen species ( Iwaniuk, Jablonska, Jablonski, Ratajczak-Wrona, & Garley, 2015 ; Jablonski, Jablonska, & Chojnowski, 2001 ; Jablonski, Jablonska, & Leonik, 2011 ; Nowak, Ratajczak-Wrona, Garley, & Jablonska, 2018 ; Ratajczak-Wrona et al, 2014 ). Impaired resolution of inflammation can lead to many human diseases including cancer ( Gartung et al, 2019 ; Panigrahy et al, 2019 ; Serhan & Levy, 2018 ; Sulciner et al, 2018 ).…”
Section: Carcinogens and Inflammationmentioning
confidence: 99%
“…One such mechanism is the generation of nitric oxide (NO) from L-arginine via the expression and activation of inducible nitric oxide synthase (iNOS; NOS2). iNOS is a dimeric protein that is expressed in several immune cells including macrophages, dendritic cells, and neutrophils (Cruz, et al, 2001, Ratajczak-Wrona, et al, 2013). The production of NO by iNOS in response to infection is a critical defense mechanism.…”
Section: Introductionmentioning
confidence: 99%